YEATS2 is a selective histone crotonylation reader - Zhao, Dan; Guan, Haipeng; Zhao, Shuai; Mi, Wenyi; Wen, Hong; Li, Yuanyuan; Zhao, Yingming; Allis, C David; Shi, Xiaobing; Li, Haitao (Cell research, 2016)
Dear Editor, Histone lysine crotonylation （Kcr） is a recently identified non-acetyl acylation conserved from yeast to human. We have previously shown that histone Kcr marked active chromatin and was enriched at promoter and enhancer regions [1]. Different from the histone ly- sine acetylation （Kac）, histone Kcr preferentially marks ＂escapee genes＂ during post-meiotic gene inactivation, suggesting a unique regulatory mechanism centered on Kcr independent of Kac [2]. Nevertheless, in contrast to the histone Kac readers that are well documented,